0324 Occupational exposure to benzene and risk of non-Hodgkin lymphoma in a population-based cohort study of Chinese women in Shanghai0324 Occupational exposure to benzene and risk of non-Hodgkin lymphoma in a population-based cohort study of Chinese women in Shanghai. (23rd June 2014) - Bassig, Bryan; Friesen, Melissa C; Vermeulen, Roel; Shu, Xiao-Ou; Purdue, Mark; Stewart, Patricia; Lu, Wei; Xiang, Yong-Bin; Chow, Wong-Ho; Zheng, Tongzhang; Ji, Bu-Tian; Yang, Gong; et al.
Abstract : Objectives: The association between benzene exposure and non-Hodgkin lymphoma (NHL) has been the subject of debate, and an IARC working group recently concluded for the first time that there is now limited evidence to support this association in humans. We evaluated the relationship between occupational benzene exposure and NHL risk among 73 087 women in a population-based cohort study of women in Shanghai. Method: Benzene exposure estimates were derived using a previously developed exposure assessment framework that combined ordinal job-exposure matrix intensity ratings with quantitative benzene exposure measurements from an inspection database of Shanghai factories collected between 1954–2000. Associations between benzene exposure metrics and NHL (n = 102) were assessed using Cox proportional hazard models, with study follow-up occurring from 1997–2009. Results: Women ever exposed to benzene had a significantly elevated risk of NHL (Hazard Ratio (HR) = 1.87, 95% CI = 1.19–2.96). Compared to unexposed women, significant trends in NHL risk were observed for increasing years of benzene exposure (ptrend = 0.009) and increasing cumulative exposure levels (ptrend = 0.01), with women in the highest duration and cumulative exposure tertiles having a significantly elevated association with NHL (HR = 2.07, 95% CI = 1.07–4.01 and HR = 2.16, 95% CI = 1.17–3.98, respectively). Conclusions: Our study is the first to our knowledge to evaluate this association in the context of a population-based prospective cohort of all women with diverse occupational histories. Our findings add to the evidence that benzene is associated with risk of NHL.